2020
DOI: 10.1093/rap/rkaa070
|View full text |Cite|
|
Sign up to set email alerts
|

Persistence of biologic treatments in psoriatic arthritis: a population-based study in Sweden

Abstract: Objectives TNF inhibitors (TNFis) and IL inhibitors are effective treatments for PsA. Treatment non-persistence (drug survival, discontinuation) is a measure of effectiveness, tolerability and patient satisfaction or preferences in real-world clinical practice. Persistence on these treatments is not well understood in European PsA populations. The aim of this study was to compare time to non-persistence for either ustekinumab (IL-12/23 inhibitor) or secukinumab (IL-17 inhibitor) to a referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 42 publications
4
19
2
Order By: Relevance
“…A similar effect of decreased efficacy in obese patients with PsA was observed in post-hoc analyses from two phase III studies of the Janus kinase (JAK) inhibitor, tofacinitib 16. Patient sex also correlates with treatment persistence,17–19 as does inadequate response to biologicals, with the use of each subsequent biological yielding successively lower rates of drug persistence 17 19–21. However, the difficult-to-treat inadequate responder subpopulation may initially experience greater efficacy responses by switching to an alternative biological following failure of ≥1 TNFi 22.…”
Section: Introductionmentioning
confidence: 70%
“…A similar effect of decreased efficacy in obese patients with PsA was observed in post-hoc analyses from two phase III studies of the Janus kinase (JAK) inhibitor, tofacinitib 16. Patient sex also correlates with treatment persistence,17–19 as does inadequate response to biologicals, with the use of each subsequent biological yielding successively lower rates of drug persistence 17 19–21. However, the difficult-to-treat inadequate responder subpopulation may initially experience greater efficacy responses by switching to an alternative biological following failure of ≥1 TNFi 22.…”
Section: Introductionmentioning
confidence: 70%
“…significantly longer treatment persistence and lower discontinuation rates compared with those initiating a TNFi during 1 year follow-up 32 and those initiating adalimumab during 10 years follow-up. 26 Likewise, the subgroup of patients with PsA in the PSOLAR Study, a registry study of 12 095 patients with psoriasis, showed better drug persistence with ustekinumab versus TNFi. 19 This difference in results of adjusted analyses between the PsABio Study and the other studies could be due to various reasons: prospective non-interventional study setting, as done here, is different from retrospective claims database or registry analysis; the ustekinumab population in the current study was heavily affected by comorbidities, chronic widespread pain, late lines of bDMARD treatment, which may have impacted drug persistence with ustekinumab in this prospective patient cohort versus the other studies, and these or additional non-assessed imbalances may not have been fully adjusted for.…”
Section: Psoriatic Arthritismentioning
confidence: 98%
“…19 A retrospective Swedish registry study with a maximum follow-up of 10.6 years demonstrated favourable persistence with ustekinumab versus adalimumab across treatment lines. 26 Six-month data from the prospective, observational PsABio cohort study of ustekinumab and TNFi treatment in patients with PsA indicated that later line of treatment, female sex and comorbidities as well as baseline disease impact, high clinical disease activity, and chronic widespread pain were shown to negatively influence treatment response. 27 Here we present data on persistence, the primary outcome of PsABio, as well as clinical effectiveness, disease impact and safety after 1 year of follow-up.…”
Section: Psoriatic Arthritismentioning
confidence: 99%
“…33 In contrast, registry-based studies such as PSOriasis Longitudinal Assessment and Registry (PSOLAR), British Association of Dermatologists Biologic Interventions Register (BADBIR), and a population study using Swedish administrative registries reported a better drug survival of ustekinumab compared with TNF inhibitors among PsA or psoriasis patients. [34][35][36] Nevertheless, data in these studies and in our study are limited to further identify specific reasons for treatment discontinuation or switching.…”
Section: Discussionmentioning
confidence: 91%